WAYS OF DEVELOPING POSITIVE GENDER ATTITUDES IN STUDENTS THROUGH SPORTS ACTIVITIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the pedagogical, psychological, and social foundations of developing positive gender attitudes among students through sports activities. In the context of modern educational reforms and globalization, gender equality has become one of the key priorities in building democratic and inclusive societies. Schools play a crucial role in shaping students’ values, social behavior, and interpersonal relationships, while physical education and sports activities provide unique opportunities for fostering cooperation, tolerance, respect, and equality among boys and girls. The study analyzes the educational potential of sports activities in reducing gender stereotypes, improving social interaction, and forming positive attitudes toward gender equality. The article highlights the role of team sports, cooperative games, inclusive physical education strategies, and student-centered pedagogical approaches in promoting equal participation and mutual respect among students. Furthermore, the research explores the importance of teachers’ gender competence and the creation of supportive educational environments that encourage students regardless of gender differences. The results of the research may serve as a theoretical and practical basis for improving physical education programs, teacher training systems, and educational policies aimed at strengthening gender equality culture among school students.